Kebijakan Hukum Pidana bagi Tindak Pidana Cyber Terrorism dalam Rangka Pembentukan Hukum Positif di Indonesia - Zephirinus Jondong (Jurnal Preferensi Hukum, 2020)
The advancement of internet-based computer technology has not only a positive impact on its users but also a negative impact, one of which is the creation of new forms of crime such as terrorism. Based on this background, this research was conducted with the aim of revealing how the regulation of criminal acts of terrorism committed through cyberspace (cyber terrorism) in positive law in Indonesia and how criminal law policies in Indonesia in the future in regulating criminal acts of terrorism committed through cyberspace (cyber terrorism). This research was designed using normative legal research methods. The results of this study reveal that in Indonesia, the criminal act of cyber terrorism is not regulated in the Criminal Code (KUHP) or the Laws and Regulations that regulate the field of terrorism. In a situation like this, the perpetrator of the crime of cyber terrorism can be declared free from punishment because there is no element against the law regulated in the Act attached to the act. Therefore, in order to be convicted of a crime, the crime of cyber terrorism must be formulated clearly. In addition, in establishing a criminal law policy regarding cyber terrorism, cyber terrorism must be considered so that it can be made a criminal act and sanctions can be imposed on the perpetrator